2019
DOI: 10.1021/acsomega.9b02756
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of New Cu Complex Based on Natural 5Z,9Z-Eicosadienoic Acid: Effective Topoisomerase I Inhibitor and Cytotoxin against the Cisplatin-Resistant Cell Line

Abstract: The complex (bipy)2Cu(5,9-eicd) was prepared by the reaction of Cu(OAc)2 with 5Z,9Z-eicosadienoic acid and 2,2′-bipyridine in methanol. The new copper complex showed high antitumor activity in vitro toward A2780cis, A2780, Hek293, K562, HL60, Jurkat, and U937 cell lines and efficiently inhibited human topoisomerase I. Using flow cytofluorometry, (bipy)2Cu(5,9-eicd) was studied for the effect on the cell cycle and apoptosis-inducing activity in tumor cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…It also has capability of inhibiting humans topoisomerase I. [138] Manish Kumar et 7) to have substantial antibacterial activity towards bacteria like Staphylococcus aureus and E. coli which are in-nature gram positive and gram negative, respectively. [139] The antibacterial activity of nalidixic acid was enhanced when it was incorporated in Cu-complex due to increased lipophilicity of Cu(II) complex of nal.…”
Section: Anticancer Active Copper Complexes With Bipyridine Ligandmentioning
confidence: 99%
See 2 more Smart Citations
“…It also has capability of inhibiting humans topoisomerase I. [138] Manish Kumar et 7) to have substantial antibacterial activity towards bacteria like Staphylococcus aureus and E. coli which are in-nature gram positive and gram negative, respectively. [139] The antibacterial activity of nalidixic acid was enhanced when it was incorporated in Cu-complex due to increased lipophilicity of Cu(II) complex of nal.…”
Section: Anticancer Active Copper Complexes With Bipyridine Ligandmentioning
confidence: 99%
“…[131] In vitro anticancer behaviour of the complex studies by SRB assay was reported to be powerful against tumor cell lines such as SMMC-7721, A549, and Hep G2 with IC 50 values of 8.8 � 0.7, 10 � 1and 4.2 � 0.4, respectively. The complex shows selective, cytotoxic [134], [135], [136], [138], and [139], respectively. For complex 81, the simplified copper coordination site given in the crystal structure of ref [137] are presented.…”
Section: Anticancer Active Copper Complexes With Bipyridine Ligandmentioning
confidence: 99%
See 1 more Smart Citation
“…For assessing the influence on topoisomerase II of the studied derivatives of hybrid molecules based on 5 Z ,9 Z -diene acids, the investigation into possible DNA damage in Jurkat tumor cells was carried out. We had previously shown that various compounds containing a diene moiety can affect their ability to inhibit topoisomerase II [ 7 , 23 , 24 , 25 , 26 , 27 , 33 , 34 , 35 , 36 , 37 , 38 ]. Changes in the concentration of total and phosphorylated proteins H2A.X allow at the same time confirming the target specificity of the phosphorylation event of this histone class.…”
Section: Resultsmentioning
confidence: 99%
“…The molecular mechanisms underlying cisplatin resistance are mainly insufficient tumor accumulation, increasing drug efflux, and increasing DNA damage repair response. , Therefore, to circumvent the Pt-based drug resistance of cancer cells, there have been five main strategies: (1) designing a metal agent based on a non-DNA target; (2) developing a non-Pt metal agent; (3) designing a multitarget metal agent; , (4) increasing intracellular drug accumulation; and (5) inhibiting the drug efflux. Moreover, many features such as macrophages in the tumor microenvironment (TME) are related to the chemotherapy resistance of tumor cells. Therefore, the development of a novel non-Pt agent based on a nanocarrier multitargeting different cell components in the TME may be promising for overcoming the resistance of cancer cells to drugs.…”
Section: Introductionmentioning
confidence: 99%